KONTRIBUSI IRIGASI PERFORASI DALAM PENYEDIAAN AIR TANAMAN DENGAN MEDIA TANAM TERBATAS: The Contribution of Perforated Irrigation to Plant Water Supply with Limited Planting Media - I Dewa Gede Jaya Negara; M Bagus Budianto; Anid Supriyadi; Kukuh Adetya (Jurusan Teknik Sipil Fakultas Teknik Universitas Mataram, 2025)
The amount of irrigation received by the plant media significantly influences the irrigation network system used. Furthermore, to determine the irrigation reach at a given head provided by the irrigation network, it is necessary to understand the irrigation distribution pattern in each pipe in the network, both the flow pattern and the irrigation quantity provided. The impact of irrigation on the land also needs to be tested to determine the characteristics of flow, distribution, and storage in the growing media. This test aims to determine the characteristics of irrigation distribution in perforated pipes and the contribution of soil moisture, its changes, and the relationship between the analyzed parameters. The irrigation test was conducted at three water level variations: 3.5 m, 3.6 m, 3.7 m, and 3.8 m. Data analysis was performed on the irrigation distribution in each perforated pipe, its quantity, and the regression relationship between the parameters. The distribution of perforated irrigation flow remained fluctuating at h1 and h3, while at h2, the flow was almost evenly distributed across the three networks. The difference in irrigation distribution relative to the average value occurred in perforation pipes 2 and 3 at h1, while the flow at perforation 1 was close to the average irrigation value. Soil moisture of 3% to 0.34% at a depth of 20 cm is estimated to be too low to support plant growth, so the duration needs to be increased. The regression relationship between w and soil moisture changes is more suitable following polynomial regression.